Development of E-Module "Community Needs Analysis" Based on Massive Open Online Course (MOOC) : Learning Innovation for Community Practitioners - Noorrizki, Rakhmaditya Dwi; Azri, Alfina Nur; Dharmastuti, Anjarie; Armalid, Ikhwanul Ihsan (Jurnal Paedagogy, 2025)
The purpose of this study was to develop a Massive Open Online Course (MOOC)-based community needs analysis e-module to improve understanding of problem-solving and community empowerment. This research used the Research and Development (R&D) method with the Four-D model (Define, Design, Develop, Disseminate). The subjects for validity, effectiveness, readability, and quality tests were content experts, material experts, and media experts. The data analysis technique used was descriptive quantitative. The material expert validity test used Aiken's V validity test analysis and Borich reliability. The validity test results obtained were 0.977 or 97.5%. The media expert validity test obtained a result of 0.844 or 84.4%. The Readability and Ease of Navigation test obtained a result of 1 or 100%. The Interactive and Feedback Quality Test obtained a result of 0.822 or 82.2%. The Media Effectiveness Test in Supporting Learning obtained a result of 0.977 or 97.7%. The results of this study indicate that the community empowerment e-module on the MOOC platform is suitable for use in communities to increase understanding of problem-solving and community empowerment training.